Adjuvant Radiotherapy Versus Watchful Waiting for World Health Organization Grade II Atypical Meningioma: A Single-Institution Experience. Issue 5 (13th May 2021) - Bray, David P; Quillin, Joseph W; Press, Robert H; Yang, Yilin; Chen, Zhengjia; Eaton, Bree R; Olson, Jeffrey J
Abstract: BACKGROUND: Atypical meningiomas (AMs) are meningiomas that have a higher rate of recurrence than grade I meningioma. Due to the higher risk of recurrence, adjuvant radiotherapy (RT) after resection of AM has been employed. At our institution, some neurosurgeons employ adjuvant RT on all primarily resected AMs, while others employ watchful waiting with serial imaging. OBJECTIVE: To study the effect of adjuvant RT on newly resected AMs. METHODS: A retrospective review of all AMs primarily resected at our institution from 1996 to 2018 was completed. Data on patient demographics, radiographic findings, use of adjuvant RT, time of follow-up, and recurrences were collected. Adjuvant RT was defined as RT that occurred within 6 mo of initial resection. RESULTS: A total of 162 patients met the inclusion criteria. Gross total resection was achieved in 73% of cases. Average time until recurrence in the cohort was 37 mo. A total of 108 patients had adjuvant RT, while 54 patients did not. On multivariate survival analysis, sex, Simpson grade resection, and use of adjuvant RT were independent predictors of recurrence. Mean time to recurrence in patients who received adjuvant RT was 43.7 mo versus 34.7 mo for those who did not receive adjuvant RT. CONCLUSION: This study includes the largest retrospective cohort of patients who have received adjuvant RT after primary resection of AM. Our results suggest that the use of adjuvant RT is independently associated with a lower chance of recurrence. These data suggest that practitioners can consider the use of adjuvant RT for newly resected AMs, regardless of Simpson grade resection. Graphical Abstract: